The K2-HERMES Survey: age and metallicity of the thick disc - Sharma, Sanjib; Stello, Dennis; Bland-Hawthorn, Joss; Hayden, Michael R.; Zinn, Joel C.; Kallinger, Thomas; Hon, Marc; Asplund, Martin; Buder, Sven; De Silva, Gayandhi M.; D’Orazi, Valentina; Freeman, Ken; et al. (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. Asteroseismology is a promising tool to study Galactic structure and evolution because it can probe the ages of stars. Earlier attempts comparing sei
Gesehen am 28.04.2020